The pedagogy of listening. Issue 7 (2nd October 2016) - Manyozo, Linje
ABSTRACT: A great deal of participatory development literature emphasises the bottom-up production of citizen's voices and their incorporation into policy formulation, implementation, and evaluation. Rarely do we hear of emphases on the question of listening, much as there exists a body of knowledge on integrating what experts consider to be the views and opinions of local people in the creation of socio-economic policies. This viewpoint outlines the kind of listening that builds on three key issues that emanate from Paulo Freire's idea of listening as both a virtue and practice of tolerance. The major contention is that as development practitioners, we need to build our abilities and capacities to practise all the three forms of listening if we are to work with others in designing and implementing policies that improve lives and communities.